Growth Performance and Carcass Characteristics of Turkeys (Meleagris gallopavo) under semi intensive System in the Sudan - Gibril, Salim; Hassan, Hafiz Abdelrahman; Yassin, Osama Elshiek (University of Khartoum Journal of Agricultural Sciences, 2023)
he objectives of this study were to determine the growth performance and carcass traits of turkeys under semi intensive system in the Sudan. Atotal of 100 unsexed turkey growers from the commercial breed (B.U.T. Big 6) were used during 7 th June to 6 th August, 2011. Birds were kept in an open sided deep litter poultry house at the University of Bahri Farm from 9 to 16 weeks of age and fed on turkey grower and finisher diets. Results of feed intake and body weight showed a consistent increase with increase in age. Performance results showed that turkey had 2.42 kg, 6.64 kg, 79.49 g, 1.5 kg/ bird/ day, 2.8 and 4%, starting weight, finishing weight, average daily gain, average feed intake; average feed conversion ratio (FCR) and total mortality, respectively. Results also showed that turkey had 6.91 kg, 5.03 kg, 76.98%, 14.37%, 14.2% and 33.4% slaughter weight, carcass weight, dressing percentage and thigh, drumstick and breast weights as percentage of carcass weight, respectively. Males obtained significantly heavier slaughter, carcass, thigh, drumstick and breast weights than females. On the other hand PH, WHC and cooking loss were 5.63, 36.6 and 2.05, respectively. It can be concluded that, the rearing of B.U.T. Big 6 commercial breed of turkey is possible under semi intensive system in the Sudan. Further studies are needed to determine turkey performance and carcass attributes under range and intensive systems of management using the same breed or other turkey breeds.